Communicating with tact, candor and credibility - Schrank, louis Schrank; Learning seed (Illinois : Learning Seed, 2008)
In this lively program, viewers see humorous, realistic situations and learn memorable, practical ways to communicate with tact, candor and credibility on the job. This program teaches how to communicate'on the level'
Title from title screen
With English subtitle
Host: Olivia Porter
Keywords: Business communiction; Interpersonal communication